Fleeting, But Not Forgotten: Ephemerality as a Means to Increase Recall of Advertising. Issue 1 (November 2021) - Campbell, Colin; Sands, Sean; Treen, Emily; McFerran, Brent
Ephemeral social media is growing in popularity and brands are increasingly using this method to engage with and advertise to consumers. Yet, little research attention has been paid to how consumers perceive and retain social media content, particularly marketing communications, when they are aware it will disappear. Across five studies we find that when viewers know content is ephemeral, their recall of the content is heightened compared to when they believe the content will be accessible later. We find that this increase in recall due to ephemerality is mediated by processing effort, such that when consumers believe content will disappear, they expend more effort processing the content than if the content is believed to be accessible again. Relevant to advertisers, we find this effect spills over to advertising embedded within ephemeral social media content. Our findings represent a novel means of increasing advertising recall, qualify past findings and theory, and suggest an important new stream of research.